2023
DOI: 10.1021/acs.macromol.2c02025
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclic Allylic Sulfone as a Universal Comonomer in Organocatalyzed Photocontrolled Radical Copolymerization with Vinyl Monomers

Abstract: Radical copolymerization of vinyl monomers and cyclic monomers is a versatile approach to degradable vinyl plastics. Despite recent advances, a class of "universal" cyclic monomers that possess broad reactivities with various types of vinyl monomers remains elusive. Herein, we report a general method for the organocatalyzed photocontrolled radical ring-opening cascade copolymerization (rROCCP) of macrocyclic allylic sulfone and various types of vinyl monomers, including acrylates, acrylamides, styrene, and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…One solution to improve the sustainability of soft materials involves synthesizing degradable polymers containing cleavable functional groups along the polymer backbone, with polyesters , and associated derivatives being prime examples. , For common vinyl monomers such as acrylates that are broadly available and applicable, the lack of intrinsic degradability has necessitated the development of novel comonomers that undergo radical ring-opening polymerization (rROP) to impart degradability. Since the 1980s, this concept has gained significant attention as a method to incorporate degradable building blocks into the backbone of otherwise intractable vinyl-based polymers. , A variety of cyclic compounds such as macrocyclic allyl sulfides (MAS) have emerged as candidates to impart degradability into various polymers. Another classic example is the copolymerization of acrylates with cyclic ketene acetals (CKA) as a method of introducing cleavable ester bonds. Despite their utility, CKAs have modest copolymerization reactivity leading to low yields and nonrandom incorporation.…”
Section: Introductionmentioning
confidence: 99%
“…One solution to improve the sustainability of soft materials involves synthesizing degradable polymers containing cleavable functional groups along the polymer backbone, with polyesters , and associated derivatives being prime examples. , For common vinyl monomers such as acrylates that are broadly available and applicable, the lack of intrinsic degradability has necessitated the development of novel comonomers that undergo radical ring-opening polymerization (rROP) to impart degradability. Since the 1980s, this concept has gained significant attention as a method to incorporate degradable building blocks into the backbone of otherwise intractable vinyl-based polymers. , A variety of cyclic compounds such as macrocyclic allyl sulfides (MAS) have emerged as candidates to impart degradability into various polymers. Another classic example is the copolymerization of acrylates with cyclic ketene acetals (CKA) as a method of introducing cleavable ester bonds. Despite their utility, CKAs have modest copolymerization reactivity leading to low yields and nonrandom incorporation.…”
Section: Introductionmentioning
confidence: 99%
“…Thioesters or esters can be installed along the backbone in a more statistical manner through copolymerization with the macrocyclic thionolactone dibenzo­[ c,e ]­oxepane-5-thione (DOT) or a macrocyclic monomer that contains an allyl alkylsulfone motif (Figure ). Additionally, it recently was shown that photolabile coumarin dimers can be installed in the main chain to enable cleavage with UVB light …”
mentioning
confidence: 99%
“…These initial demonstrations of depolymerization are expected to be applied for a wider scope of polymers (i.e., prepared from nonmethacrylic monomers and various CTAs) under milder reaction conditions. Combined with the synthesis of degradable vinyl polymers via copolymerization with macrocyclic allylic sulfones, 100,185 radical-mediated depolymerization would provide further opportunities for polymer chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that PET-RAFT polymerization provided high tolerance of functional groups incorporated into monomers (Scheme 18). For example, by PET-RAFT polymerization using Ir(ppy) 3 100 or EY, 185 macrocyclic allylic sulfones, which introduce degradable ester bonds along the polymer backbone, could be evenly distributed within a nearly ideal random copolymer of macrocyclic allylic sulfones and acrylic monomers, which otherwise is not achieved by thermally initiated RAFT polymerization. The even distribution of degradable moieties along the copolymers led to significantly improved degradation behaviors.…”
Section: Pet-raft Polymerizationmentioning
confidence: 99%